Investigation of diffusive transport of radon through bricks - Soniya, S.R.; Abraham, S.; Khandaker, Mayeen Uddin *; Jojo, P.J. (Elsevier, 2021)
Radon and their progeny are known indoor lung carcinogens with major sources from the subsoil followed by building materials. The present work was aimed to study the radon permeability of main building materials which is a dominant process for radon entry to indoor environment under normal room conditions. For this purpose, the radon diffusion coefficient and permeability for widely used bricks in the southern coastal region of India were measured with a specially designed twin-chamber experimental set up: a strong source of radon in one chamber and radon and progeny accumulation arrangement in another chamber. Brick samples (with varying thicknesses, firing time and porosity) collected from local kilns were sandwiched between the chambers allowing the radon gas to diffuse through them to get developed in the second chamber. An alpha scintillation based radon monitoring device was connected with both chambers for online radon measurement. Moderately- and lightly-fired bricks show relatively greater permeability than the highly-fired ones, but all the studied bricks are found to be in the radon-tight category. Measured data of radon diffusion coefficient (0.29–0.40) × 10−6 m2s-1 with a mean of (0.35 ± 0.05) × 10−6 m2s-1 and diffusion length (0.37–0.44 m) with a mean of 0.41 ± 0.03 m show a general agreement with the available results in the literature, albeit differing with an earlier study by Chauhan et al. (2008) due to the variation of the sample matrix. Measured data may help the building construction agency to choose a suitable brick to ensure a safer indoor environment for the dwellers.